Mason, The Dissolution Of The Austro-Hungarian Empire, 1867-1918 - Reinhartz, Denny (Teaching History: A Journal of Methods, 1998)
Albeit significant, traditionally Central Europe has been a rather complicated region for students and others less well informed to comprehend historically and in the present. Moreover, since the era of glasnost and the fall of the Soviet Empire this complexity has seemingly intensified. A similar situation existed in the late nineteenth and early twentieth centuries, especially with regard to the demise of the then once great empires still overlaying the region-German, Russian, Turkish, and Austro-Hungarian.